Nutritional, sensorial, and microbiological quality of canned pirarucu fillets from wild fishing and pisciculture (Research, Society and Development, 2024)
Pirarucu (Arapaima gigas) is one of the largest freshwater fish in the world. Dried salted fillet of pirarucu is the main product commercialized in northern Brazil, whereas frozen and smoked fillets are less frequently available. The present study aimed to produce canned pirarucu from wild fishing and pisciculture to add value, encourage fish consumption, and diversify canned fish products, as well as to subsequently evaluate the microbiological quality and physicochemical and sensorial characteristics these products. The fillets were sanitized in chlorine solution, immersed in brine (3% refined salt), drained, cut, and packed in cans. Thereafter, 2% hot brine was added, and the cans were subjected to exhaustion, seaming, thermal treatment, and cooling. The containers that revealed no bulging, pinholes, or leaks, and pH